2020
DOI: 10.3390/ijms21249442
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the miR-371/372/373 miRNA Cluster Enhances Oncogenicity and Drug Resistance in Oral Carcinoma Cells

Abstract: Oral squamous cell carcinoma (OSCC) is among the leading causes of cancer-associated deaths worldwide. Family members in miR-371/372/373 miRNA cluster, which is localized at human chromosome 19q13.4, are co-expressed in both human stem cells and malignancies. The individual miRNA in this cluster are also involved in modulating the pathogenesis of malignancies as either oncogenes or suppressors. The 19q13 region is frequently gained in head and neck cancers. High expression of miR-372 and miR-373 are survival p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A recent study on oral carcinoma cells showed that the miR-371/372/373 cluster could be removed using CRISPR/Cas9 technology. The results of this study showed that this deletion significantly enhances the apoptotic effects of cisplatin so that, in deleted subclones, the population of late apoptosis increases significantly after 48 h of treatment with 15 μM cisplatin [143]. One study showed that, using CRISPR/Cas9 technology and lentiviral vector, the expression of miR-21, a well-known oncomiR, in ovarian cancer cells could be inhibited.…”
Section: Crispr/cas9 Gene Editing Applications In Overcoming Drug Res...mentioning
confidence: 87%
“…A recent study on oral carcinoma cells showed that the miR-371/372/373 cluster could be removed using CRISPR/Cas9 technology. The results of this study showed that this deletion significantly enhances the apoptotic effects of cisplatin so that, in deleted subclones, the population of late apoptosis increases significantly after 48 h of treatment with 15 μM cisplatin [143]. One study showed that, using CRISPR/Cas9 technology and lentiviral vector, the expression of miR-21, a well-known oncomiR, in ovarian cancer cells could be inhibited.…”
Section: Crispr/cas9 Gene Editing Applications In Overcoming Drug Res...mentioning
confidence: 87%
“…Researchers have proposed that clustered miRNAs can act more efficiently than a single miRNA, as a cluster contains multiple miRNAs (Wang et al 2016 ). Clustered miRNAs deregulation is more potent and crucial in cancer signaling pathways and is further responsible for clinical complications such as resistance to therapy (Lin et al 2020 ; Becker et al 2012 ). Hence, the role of clustered miRNAs as a biomarker for diagnosis, prognosis, treatment, and improved patient care remains to be fully exploited.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-371/372/373 miRNA cluster is located on human chromosome 19q13.4, which is frequently acquired in head and neck cancers [ 122 ]. Additionally, expression of miR-372 and miR-373 is correlated with poor prognosis in OSCC patients.…”
Section: Apoptosismentioning
confidence: 99%